Integration of Innovative Concepts in Improving Organizational Competitiveness: Systematic Literature Review - Hosnaidah, Hosnaidah; Anshori, Mochammad; Andriani, Nurita (Economic and Business Horizon, 2023)
In the competitive business world, strategy is crucial to compete and thrive. There are three approaches that can be taken: first, becoming a low-cost producer, second, differentiating products and services in areas where competitors have not yet reached, and third, changing market segments to influence the level of competition. The importance of these strategies prompted the use of Systematic Literature Review (SLR) in management research. This method gathers the latest findings related to innovation in the management paradigm, enabling a comprehensive understanding from multiple sources. Innovation is an important point in improving economic competitiveness. In addition to driving economic growth and productivity, innovation also creates jobs and strengthens dynamic and sustainable economic development. A country's capability to provide global products at competitive prices determines its competitiveness. Developed countries maintain their position through high innovation, while developing countries often lag. Investment is needed, both in an enabling climate, increased research funding, and regulations that encourage the emergence of new ideas, so that developing countries can keep up with the competition.